Progressive Clinical and Neuroradiological Findings in a Child with BCL11B Missense Mutation: Expanding the Phenotypic Spectrum of Related Disorder - Alfei, Enrico; Cattaneo, Elisa; Spaccini, Luigina; Iascone, Maria; Veggiotti, Pierangelo; Doneda, Chiara (Neuropediatrics, 2021)
We report a patient affected by BCL11B-related disorder, providing the first extensive demonstration of clinical and neuroradiological progressive course of the disease, with possible implications on the way it is studied and followed-up. Never described clinical aspects such as toes abnormalities and hypospadias widen the range of dysmorphisms associated with this condition. Our data suggest that BCL11B mutations may be implicated not only in impaired morphogenesis and hematopoiesis but also in progressive central nervous system damage, which remains to be further investigated and clarified.
Keywords: BCL11B; neurodevelopmental disorder; brain; basal ganglia; dystonia; immunodeficiency